An examination of how alcohol enforcement strategies by sheriff and police agencies are associated with alcohol-impaired-driving fatal traffic crashes. (18th August 2021) - Lenk, Kathleen M.; Erickson, Darin J.; Joshi, Spruha; Calvert, Collin; Nelson, Toben F.; Toomey, Traci L.
Abstract: Objective: Over 10, 000 people die in alcohol-impaired-driving traffic crashes every year in the U.S. Approximately half of alcohol-impaired drivers report their last drink was at a bar or restaurant, and most bars and restaurants serve alcohol to patrons who are already intoxicated, known as overservice. Law enforcement agencies use various strategies to address alcohol-impaired driving and overservice but research on the effectiveness of these strategies is limited. Our objective was to assess whether law enforcement efforts focusing on alcohol-impaired driving and alcohol overservice were associated with alcohol-impaired-driving fatal traffic crashes. Methods: We conducted a survey of police and sheriff agencies in 1, 082 communities across the U.S. in 2010 regarding their alcohol enforcement practices. We assessed whether the agency conducted: (1) alcohol overservice enforcement and (2) alcohol-impaired driving enforcement (sobriety checkpoints, saturation patrols, open container, overall alcohol-impaired driving enforcement). From the Fatality Analysis Reporting System (2009–2013), we obtained counts of alcohol-impaired-driving fatal traffic crashes (at least one driver had blood alcohol content ≥ 0.08) within the agency's jurisdiction boundary and within a 10-mile buffer. Using multi-level regression, we assessed whether each enforcement type was associated with alcohol-impaired-driving fatal crashes (per 100, 000 population). For both the jurisdiction boundary and 10-mile buffer, we ran stratified models based on community/agency type: (1) small town/rural police; (2) urban/suburban police and (3) sheriffs. Results: In jurisdiction boundary models, urban/suburban communities where police conducted overservice enforcement (compared to those that did not) had fewer alcohol-impaired-driving fatal crashes (5.0 vs. 6.6; p = 0.01). For the 10-mile buffer, small town/rural communities where police agencies conducted overservice enforcement (compared to those that did not) had fewer alcohol-impaired-driving fatal crashes (16.9 vs. 21.2; p = 0.01); we found similar results for small town/rural communities where police used saturation patrols (18.7 vs. 22.1; p = 0.05) and had overall high alcohol-impaired driving enforcement (18.7 vs. 22.1; p = 0.05). The direction and the size of the effects for other types of enforcement and agencies were similar, but not statistically significant. Conclusions: Alcohol enforcement strategies among police agencies in small town/rural communities may be particularly effective in reducing alcohol-impaired fatal traffic crashes. Results varied by enforcement, agency and community type.